Cuckoo in the Nest? Australian Military Historiography: The State of the Field - Grey, Jeffrey (History compass, 2008)
Military history in Australia presents a paradox: a field with a healthy popular profile and high-level political endorsement but which attracts decidedly mixed interest amongst university-based historians. This article surveys the current state of the field and examines the legacy of the official history tradition, the recent re-emergence of populist ‘blockbusters’, the academic historians’ emphasis upon memory, commemoration and the history of emotions, and military biography. The article concludes by noting the divide between historians whose work concentrates on operations, technology, logistics and doctrine and those, mostly academic, historians whose chief influence is social history.